Sex Differences in the Relationship Between School Bullying Victimization and Complex Posttraumatic Stress Disorder: The Roles of Insecure Attachment - Li, Yuchen (Journal of interpersonal violence, 2024)
School bullying victimization is a highly concerning issue that can lead to a range of negative outcomes. Despite the research showing a significant association between bullying victimization and complex posttraumatic stress disorder (CPTSD), the internal mechanisms with its two components (i.e., posttraumatic stress disorder symptoms [PTSD] and disorders of self-organization symptoms [DSO]) remain unclear. Previous studies have indicated that attachment style may influence the development of CPTSD symptoms and that there may be sex differences in attachment styles. Thus, the present study aims to examine the mediating role of insecure attachment between school bullying victimization and CPTSD symptoms in males and females. The study assessed bullying victimization, attachment orientation, and CPTSD (i.e., PTSD symptoms and DSO symptoms) symptoms in 675 college students (65.2% females; Mage = 19.6, SD = 1.34) from China who had reported bullying experiences at two different time points, 6 months apart. For females, school bullying victimization predicted PTSD and DSO symptoms through attachment anxiety and only predicted DSO symptoms through attachment avoidance. For males, we found that school bullying victimization predicted PTSD symptoms through attachment avoidance. These findings suggest that attachment is critical in understanding how school bullying victimization may lead to CPTSD symptoms among individuals of different sexes.